The Petrov affair : politics and espionage - Manne, Robert (Pergamon, 1987)
The Petrov Affair: Politics and Espionage is a memoir of the Petrov Affair, a historical event that involves the defection of Vladimir Petrov, a colonel in the Soviet intelligence service in Sydney, and the announcement of his defection ten days later by Australian Prime Minister Robert Menzies.